El restabliment de la Companyia de Jesús a València. - MONJO I DALMAU, FRANCESC-JOAN (Scripta, 2018)
The expulsion of the Society of Jesus, decreed by Charles III of Spain in 1767, initiated a long period of darkness for the Hispanic Jesuits. Although the coup de grace to the order would come by the hands of Pope Clement XIV, who was pressured by the Spanish monarchy (the ambassador of the Hispanic king in Rome Moñino resorted to the coercion and subornation of those who were related to the pontiff), declared the Society extinguished on July 21, 1773. The suppressed Jesuits produced propaganda for more than forty years to reverse the situation. Finally, in 1814 Pope Pius VII restored the Jesuit Order around the world through the Bull Sollicitudo omnium ecclesiarum, and one year later the regular Ignatians obtained the desired permission from Ferdinand VII to return to the Hispanic territories. On July 18, 1816, the Jesuits took possession of Casa Professa, now converted into a school.